DNA barcoding of pear psyllids (Hemiptera: Psylloidea: Psyllidae), a tale of continued misidentifications - Cho, G; Malenovský, I; Burckhardt, D; Inoue, H; Lee, S (Bulletin of entomological research, 2020)
Pear psyllids (Hemiptera: Psylloidea: Psyllidae: Cacopsylla spp.) belong to the most serious pests of pear (Pyrus spp.). They damage pear trees by excessive removal of phloem sap, by soiling the fruits with honeydew which, in turn, provides a substrate for sooty mould, and by transmission of Candidatus Phytoplasma spp., the causal agents of the pear decline disease. The morphological similarity, the presence of seasonal dimorphism that affects adult colour, size and wing morphology and uncritical use of species names, led to much confusion in the taxonomy of pear psyllids. As a result, pear psyllids have been frequently misidentified. Many of the entries attributed to Cacopsylla pyricola and other species in the GenBank are misidentifications which led to additional, unnecessary confusion. Here we analysed DNA barcodes of 11 pear psyllid species from eastern Asia, Europe and Iran using four mitochondrial gene fragments (COI 658 bp, COI 403 bp, COI-tRNAleu-COII 580 bp and 16S rDNA 452 bp). The efficiency of identification was notably high and considerable barcoding gaps were observed in all markers. Our results confirm the synonymies of the seasonal forms of Cacopsylla jukyungi ( = C. cinereosignata, winter form) and C. maculatili ( = C. qiuzili, summer form) previously suggested based on morphology. Some previous misidentifications (C. chinensis from China, Japan and Korea = misidentification of C. jukyungi; C. pyricola and C. pyrisuga from East Asia = misidentification of C. jukyungi and C. burckhardti, respectively; C. pyricola from Iran = misidentification of C. bidens, C. pyri and Cacopsylla sp.) are also corrected. There is no evidence for the presence of European pear psyllid species in East Asia.
Keywords: druhová specificita; Animals; hmyzí geny; taxonomické DNA čárové kódování; DNA Barcoding, Taxonomic; Genes, Mitochondrial; Genes, Insect; zvířata; Hemiptera; Species Specificity; mitochondriální geny